Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae) - Tian, Mingyi; Huang, Xinglong; Li, Chenliang (Zootaxa, 2021)
Two new genera and three new species of troglobitic trechine beetles are described and illustrated from the eastern part of Wuling Mountains: Xiangxius jiangi n. gen., n. sp. and Guizhaphaenopsodes solidior n. gen., n. sp. from the limestone cave Tangle Dong (Jishou, western Hunan Province); Sinotroglodytes hefengensis n. sp. from the limestone cave Qizimei Dong (Hefeng, southwestern Hubei Province). Xiangxius jiangi is a highly modified cave-adapted beetle with elongate body and appendages, recognized by its peculiar elytral shape and remarkable dorsal and marginal umbilicate pores of elytra. Guizhaphaenopsodes solidior is peculiar for its stout body, robust antennae and pigmented forebody, antennae and legs though it shares several generic important characteristics with the genus Guizhaphaenops Vigna Taglianti, 1997. Sinotroglodytes hefengensis has an elongated and parallel-sided head.